Features of entropy analysis of measurement results in nonlinear dynamical systems - Machekhin, Yu. P.; Kurskoy, Yu. S. (Метрологія та прилади, Харьков, 2013)
This article is the first from the group of publications about new metrological tasks. The article contains the arguments for using entropy analysis during creation new specific approaches and models for measurements in real-world nonlinear dynamical systems. The presenters offer special measurement model and measurement results analysis model that based on the main principles and concepts of dynamical chaos theory and fractal representations of the real systems behavior. The example of entropy analysis of measurement results in nonlinear dynamical systems is represented. It is shown that using entropy analysis will allow to use the modified Concept of expression of uncertainty of measurements in real-world, open, dissipative, chaotic systems.
Keywords: measurements; nonlinear dynamical systems; chaos